2020
DOI: 10.3390/molecules25174002
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Amphotericin B-Loaded Chitosan Nanoparticles against Experimental Cutaneous Leishmaniasis

Abstract: Chitosan nanoparticles have gained attention as drug delivery systems (DDS) in the medical field as they are both biodegradable and biocompatible with reported antimicrobial and anti-leishmanial activities. We investigated the application of chitosan nanoparticles as a DDS for the treatment of cutaneous leishmaniasis (CL) by preparing two types of chitosan nanoparticles: positively charged with tripolyphosphate sodium (TPP) and negatively charged with dextran sulphate. Amphotericin B (AmB) was incorporated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Therefore, Cs-NPs could enhance the antileishmanial activity of LP. Similar results were observed for amphotericin B incorporated into chitosan nanoparticles which were more potent than free amphotericin B in inhibiting leishmania major promastigotes and amastigotes [45]. LP/Cs-NPs showed less toxicity than LP to human red blood cells and Raw 264.7 cells.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, Cs-NPs could enhance the antileishmanial activity of LP. Similar results were observed for amphotericin B incorporated into chitosan nanoparticles which were more potent than free amphotericin B in inhibiting leishmania major promastigotes and amastigotes [45]. LP/Cs-NPs showed less toxicity than LP to human red blood cells and Raw 264.7 cells.…”
Section: Discussionsupporting
confidence: 78%
“…The accumulation of phagocytes from inflammation in infected tissues may have contributed to the increased nanoparticle uptake observed in infected tissues after topical administration. On the contrary, intravenous administration of AmpB-CHI increased the intralesional concentration of AmpB and decreased parasite burden in comparison to LAmpB treatment (Riezk et al, 2020).…”
Section: Leishmaniasismentioning
confidence: 84%
“…Recently, Riezk et al . evaluated the in vitro antileishmanial activity of various forms of chitosan, including low, medium and high molecular weight chitosan and its derivatives, against extracellular promastigotes and intracellular amastigotes of L. major and L. mexicana [32] . In this study, the authors demonstrated for the first time a pH dependent antileishmanial activity of chitosan and its derivatives, which may justify the great variability of the antileishmanial activity of this compound in the literature.…”
Section: New Molecules With Potential For Treatmentmentioning
confidence: 83%